Analisis Kompetensi Kerja Karyawan di PT Bridgestone Tire Indonesia Departement Produksi Seksi Bead - Riyandi Rahman Hidayatulloh; Uus MD Fadli; Laras Ratu Khalida (Universitas Batanghari, 2023)
This research study aims to determine the work competence of employees at PT Bridgestone Tire Indonesia in the Bead Section Production Department through the use of the Importance and Performance Analysis (IPA) method. In this research study, the authors used quantitative research methods. technical analysis of data using the method of importance performance analysis (IPA). The data used in this study are primary data. In this study the sampling method was obtained through saturated sample techniques. The population used was employees at PT Bridgestone Tire Indonesia Bead Department with a total sample of 80 people, sample collection using a questionnaire distributed via google form to all members of the population of PT Bridgestone Tire Indonesia Bead Department. The results of this study show that the level of competence of employees at PT Bridgestone Tire Indonesia is in a fairly good position